1997
DOI: 10.1073/pnas.94.24.13203
|View full text |Cite
|
Sign up to set email alerts
|

Loss of ovarian function promotes angiogenesis in human ovarian carcinoma

Abstract: We show here that elevated levels of gonadotropins (luteinizing hormone and follicle stimulating hormone), as found in menopause or after ovariectomy, promote growth of human ovarian carcinoma by induction of tumor angiogenesis. Human epithelial ovarian cancer tumors progressed faster in ovariectomized mice. This induced growth could be attributed to the elevated levels of gonadotropins associated with loss of ovarian function because direct administration of gonadotropins also was effective in promoting tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
84
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 21 publications
2
84
0
1
Order By: Relevance
“…18,19 Moreover, it has been suggested that loss of ovarian function promotes tumorigenesis by resulting in increased gonadotropins, which promote vascularization via increased levels of VEGF. 20 Recent data also have supported the finding that testosterone replacement in castrated rats increases mRNA levels of VEGF. 21 This phase 2 study evaluated the hypothesis that the inhibition of the androgen axis could result in a decrease in tumor recurrence by inhibiting AR, reducing circulating gonadotropins, and suppressing androgen-mediated VEGF production.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…18,19 Moreover, it has been suggested that loss of ovarian function promotes tumorigenesis by resulting in increased gonadotropins, which promote vascularization via increased levels of VEGF. 20 Recent data also have supported the finding that testosterone replacement in castrated rats increases mRNA levels of VEGF. 21 This phase 2 study evaluated the hypothesis that the inhibition of the androgen axis could result in a decrease in tumor recurrence by inhibiting AR, reducing circulating gonadotropins, and suppressing androgen-mediated VEGF production.…”
supporting
confidence: 55%
“…VEGF levels were found to have considerable interpatient variability and did not exhibit decreases as a result of suppression of the androgen axis, as hypothesized. 20 FIGURE 2. Serum levels of (A) luteinizing hormone (LH; in mIU/mL), (B) follicle-stimulating hormome (FSH; in mIU/mL), (C) vascular endothelial growth factor (VEGF; in pg/mL), (D) testosterone (TEST; in ng/dL), and (E) androstenedione (ANDRO; in ng/dL).…”
Section: Discussionmentioning
confidence: 99%
“…These hormones have been shown to stimulate the growth of normal and [35,36]. However, little was known about the mechanism of FSH stimulation on VEGF expression.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these observations, whether gonadotropins may play a role in normal OSE biology and ovarian tumorigenesis remains to be fully elucidated and the exact mechanism of the response to gonadotropins is not clearly understood. The growth of human ovarian carcinoma has been promoted by elevated levels of gonadotropins through induction of tumor angiogenesis in vivo (Schiffenbauer et al 1997, Zygmunt et al 2002, and the level of vascular endothelial growth factor (VEGF) was significantly elevated in both low malignant potential (LMP) and serous ovarian carcinoma (Wang et al 2002). In addition, gonadotropin-induced stimulation results in an increase in the expression of integrin subunit alpha (v) and CD44, the cell surface hyaluronan receptor in MLS human epithelial ovarian carcinoma cells (Schiffenbauer et al 2002).…”
Section: Discussionmentioning
confidence: 99%